Multi-Criteria Spatial Analysis of Hazardous Materials Transportation - Cordeiro, Francyelly Giovany [UNESP]; Bezerra, Barbara Stolte [UNESP]; Peixoto, Anna Silvia P. [UNESP]; Kaiser, Ilza Machado [UNESP] (American Society of Civil Engineers (ASCE), 2014)
The development of the world economy increases trade, thereby inducing a large amount of goods transportation. In many developing countries, such as Brazil, the transportation system is predominated by the highway mode. Municipal highways, most of time, are part of the main road cargo transportation system, and this makes the traffic of hazardous materials a risk to society and the environment. The goal of the paper is the use of a multi-criteria analysis methodology, for modeling of the environmental risk of Road Transport of Hazardous Materials (RTHM) in Sao Paulo State - Brazil. Therefore, a methodological discussion is presented to explore the issues inherent to the composition of the panel of experts to assign weights to each criterion and to quantify the relative importance of each for risk analysis of environmental damage.
Keywords: environmental risk; Hazardous material; modeling risk; multi-criteria analysis; road accidents